LEGAL RESPONSIBILITY OF VACCINE PROVIDER ON THE IMPACT OF POST IMMUNIZATION FOLLOWING EVENT (AEFI) AFTER VACCINATION - Willy Tanjaya; Tommy Leonard; Leonardus Mirzal Lumban Gaol (Magister Kenotariatan Universitas Pasundan, 2022)
Health has a broad meaning and dimension according to the definition according to WHO and the Health Law, namely a healthy state which includes physical, mental, spiritual and social aspects and can be socially and economically productive. This shows that a person's health status is not only measured from physical and mental aspects, but is also assessed based on social or economic productivity. In early 2020 the world was shocked by the outbreak of a new virus named by the World Health Organization (WHO) Severe Acute Respiratory Syndrome Coronavirus-2 and the name of the disease as corona virus disease 2019 (Covid-19). One way to suppress its growth rate is that the Central Government will take action to vaccinate people in Indonesia so that the spread of the Covid 19 virus does not increase. However, Recently, there have been several reports related to the administration of vaccines with the type of vaccine that experiences a lot of Post-Immunization Adverse Events (AEFI) such as fever, chills, headache, and body aches and weakness. For the impact of the AEFI, the public often blames health workers and even accuses them of medical malpractice In the implementation of the COVID-19 vaccination, it is also obligatory for every citizen to vaccinate. Regulation of the Minister of Health of the Republic of Indonesia Number 10 of 2021 concerning the Implementation of Vaccination in the Context of Combating the 2019 Corona Virus Disease (Covid-19) Pandemic Article 46 Paragraph (1), Paragraph (2), and Paragraph (3) then the government has legal responsibility, if the vaccine organizers follow the Operational Standards that have been established.It is recommended to the central government in issuing new rules related to the handling of Covid 19 and the implementation of vaccinations must be in line with and must not conflict with existing laws and regulations, especially regarding Human Rights (HAM) and the rights of citizens to determine systems and procedures. ways to maintain their health in a responsible manner, including vaccination, which should be one of the choices in health care society and not to be forced.